Data Monitoring System- based Framework for PV Charging Management Applications - Muneer Mansoor (Peneliti Teknologi Teknik Indonesia, 2023)
Enhancing the efficiency of Management Applications requires a monitoring system. The industrial device monitoring process greatly benefits from the physical verification of the process taking place with the data instrument. The use of automated sensor controllers, Photovoltaic (PV) Management Applications, etc. is sometimes used to carry out monitoring tasks. the widespread use of computerized data controllers to handle process halts brought on by broken electrical equipment. A screen will show the status once an intelligent controller has total control over the system. Physical switches allow a human operator to control specific processes and equipment based on their quality. The design uses the Internet and the Blynk server for specific operations. Based on the preliminary results obtained by implementing our framework system, the possibility of managing and monitoring PV charging applications and improving the energy utilization efficiency of control devices may be possible.